(untitled) (Journal of history-rus, 2021)
This article discusses the consistent development of cooperation between the Republic of Uzbeki- stan and Central Asian countries. The importance of making the Central Asian region a priority of Uz- bekistan’s foreign policy was highlighted. It was explained that the centuries-old brotherhood of Central Asian peoples, common history, spiritual and cultural values, similar traditions and customs play a role in strengthening regional cooperation. It has been shown that its implementation contributes to the de- velopment of security, stability and economic integration processes in the Central Asian region. The fac- tors contributing to the further strengthening of friendly and trusting relations between Uzbekistan and Kazakhstan, Kyrgyzstan, Tajikistan and Turkmenistan were also analyzed. When analyzing the issues of economic cooperation between Uzbekistan and the countries of the region, special attention was paid to transport communications, and the important strategic position of the Central Asian states requires the rational use of international transport corridors. The specificity of such types of transport communication as railway, aviation and automobile is shown. They also analyzed the practical initiatives of Uzbekistan to strengthen regional cooperation. In particular, the beginning of a new era in the cooperation of Uz- bekistan with Central Asian countries since 2017 has been studied. Conclusions were reached on the transformation of Central Asia into the main priority of the foreign policy of the Republic of Uzbekistan, and a number of proposals were made to strengthen cultural cooperation. Key words. Republic of Uzbekistan, Central Asia, cooperation, Foreign policy, Action strategy, con- sultations, summit, good neighborly environment, prosperity belt, priorities, general history, stability, sustainable development, good neighborliness, universal values.